Influence of Cognitive Agility of Cyber Operators on Situational Aware Cyberspace Protection - Njoga, David A.O.; Liyala, Samuel; Abeka, Silvance (International Journal of Innovative Research and Advanced Studies (IJIRAS), 2022)
The effectiveness of the cyberspace protection for the national critical information infrastructure (CII) depends on a dynamically and reliably established cyberspace situational awareness framework. The current attribution based cyberspace protection models and frameworks are characterised by over dominance of government agencies and laws, overreliance on technology and lack of trust, transparency and goodwill leading to weak protection of critical information infrastructure. The study adopted a descriptive survey research design, in which conveniently sampled participants answered questions administered through Self-Regulation Questionnaires through three stage Delphi-Technique evaluation. Data was then analyzed using mean, standard deviation, frequency distributions, Pearson’s correlations and Linear Regression Analysis. The study revealed that there was a statistically significant moderate and positive association /relationship between cognitive agility and situational-awareness. This implies that the cyberspace protection is as strong or as weak as the cyberspace protection operators. The study concluded that a human-factored security endeavour is required that can improve the capabilities of the operational technology human constituents, so that they can appropriately recognise and respond to cyber intrusion events within the CII environment. Amidst evolving security trends that places human industrial actors as prime vectors of CII cyber-attacks, human-factored security efforts are required to manage and control the menace of prevailing attacks. It’s invaluable considering that cyber security knowledge and skills capabilities of the CII workforce (people) is crucial and strategic towards building a more effective and cyber security-compliant workforce. Cognitive agility is a major contribution to cyberspace’s protection since cyberspace is a fluid, technically changing environment, continuously increasing in scale and sophistication that must be constantly supervised and redefined by actors’ stable presence. These findings provide a human centred security capability and resilience building model which can be used to strengthen the security aptitude of human agents within CII. Noting the ‘standardization’ and ‘accountability’ common to traditional education models, this study recommends new and likened pedagogical interventions which provide the context for new literacies that include metacognitive strategies such as critical thinking, complex problem solving, expert communication and applied knowledge in real world settings. Inspired by constructivism, and the slow education approach to learning, specific pedagogical interventions designed to improve higher-order thinking and understanding, such as self-directed workshops, flipped classroom, reflection logs, and cognitive task analysis. An outcome of this method is students gaining situational self-efficacy and empowerment as they engage in critical thinking. This is valuable for cyber education as it leads learners to exhibit and contextualize richer relationships and meanings beyond the prescribed lesson content.
Keywords: Cyberspace; Cognitive; Critical; Human